Júlia Lourenço (PT) : Universidade do Minho - (:unkn) unknown (AESOP, 2011)
Have a PhD on Regional and Territorial Planning (IST. Lisbon 1997) and is Professor at Universidade do Minho, Portugal, and former Director of Civil Engineering graduate studies at Minho University and actually is Director of Municipal Engineering Master Course. Has been developing pedagogical experiences about knowledge by project, peer evaluation and team work on urban planning and management field.
Quality of Space – Quality of Life : Planning for Urban Needs of diverse timeframes. 2nd AESOP European Urban Summer School 2011, Lisbon